THE EFFECT OF USING PAIR REHEARSAL TECHNIQUE TOWARD STUDENTS’ SPEAKING PARTICIPATION (STUDY AT THE XI TH CLASS OF SMANEGERI 06 KOTA BENGKULU) - Gultom, Lia Christina; Puspita, Hilda; Hati, Gita Mutiara (Journal of English Education and Teaching, 2018)
The objective of this research was to investigate whether there was an effect of the implementation of Pair Rehearsal Technique toward students’ speaking participation. The research was designed as pre-experimental research by using pre-treatment and post-treatment group. The research was conducted at the eleventh IPA grade of SMA Negeri 06 Kota Bengkulu. Random sampling was a technique to take the class. The data were collected through an observation checklist which was adapted from Boyd et al (2007), Vandrick (2000), Teacher Handbook of the National University of Singapore, (NUS, 2009) in Abuid (2014). The result of this research showed a positive effect on students’ speaking participation in verbal and non-verbal participation in the post-treatment rather than in pre-treatment. Nevertheless, students were tended to participate in non-verbal participation.